Selective recovery of silver from waste low-temperature co-fired ceramic and valorization through silver nanoparticle synthesis. (November 2017) - Swain, Basudev; Shin, Dongyoon; Joo, So Yeong; Ahn, Nak Kyoon; Lee, Chan Gi; Yoon, Jin-Ho
Graphical abstract: Highlights: Silver rich LTCC an e-waste has been recycled and valorized. Selectively, Ag was leached and recovered as nanopowder. The process can circulate the Ag within the industry in a close loop. Brings back the material to production stream and address the circular economy. Can be part of cradle-to-cradle technology and lower the futuristic carbon economy. Abstract: Considering the value of silver metal and silver nanoparticles, the waste generated during manufacturing of low temperature co-fired ceramic (LTCC) were recycled through the simple yet cost effective process by chemical-metallurgy. Followed by leaching optimization, silver was selectively recovered through precipitation. The precipitated silver chloride was valorized though silver nanoparticle synthesis by a simple one-pot greener synthesis route. Through leaching-precipitation optimization, quantitative selective recovery of silver chloride was achieved, followed by homogeneous pure silver nanoparticle about 100 nm size were synthesized. The reported recycling process is a simple process, versatile, easy to implement, requires minimum facilities and no specialty chemicals, through which semiconductor manufacturing industry can treat the waste generated during manufacturing of LTCC and reutilize the valorized silver nanoparticles in manufacturing in a close loop process. Our reported process can address issues like; (i) waste disposal, as well as value-added silver recovery, (ii) brings back the material to production stream and address the circular economy, and (iii) can be part of lower the futuristic carbon economy and cradle-to-cradle technology management, simultaneously.